Didactic integration of physical education and educational activities in the conditions of public service universities - Mironov A.O. ,; Belyakova M.Yu. ,; Spiridonov E.A. ,; Fetisov V.N. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to develop and justify a model of combined learning that provides opportunities for stable and continuous development of sports skills and educational competencies. Methods and structure of the study. Algorithmization of organizational and educational activities in iterations of project management has been implemented. Observations were carried out to assess the dynamics of professional competencies and sports readiness of 37 students (15 boys and 22 girls), aged 20,5±0,5 years. Results and conclusions. Structuring educational and sports training activities in the areas of management functions of physical culture and sports management forms a high level of professional competencies and sports preparedness of student-athletes. Scaling multi-criteria tasks for training management personnel, synchronizing the processes of educational and sports activities of students, achieving a balance between basic and additional educational programs for training specialist managers, determine the representativeness of sources for increasing the professional and physical potential of management students.